PENGARUH PEMBERIAN RHODAMIN B TERHADAP SIKLUS ESTRUS MENCIT (Mus musculus L.) BETINA - Febrina, G.A.A Rina; Wiratmini, Ngurah Intan; Sudatri, Ni Wayan (Jurnal Biologi Udayana, 2013)
The research was conducted to identify the effect of rhodamine B on estrous cycle on female mice ( Mus musculus L.). Twenty-four female mice were used, and randomly divided into four groups.  Rhodamine B was given orally (gavage) with a dose of  0 ppm (control), 150 ppm, 300 ppm, and 600 ppm in two estrous cycles.  Treatments were started when mice in estrus phases. The time between first and the next estrus phase were observed from vaginal smear preparation. Data obtained were analysed with One Way Anova.  If the differences were appeared between treatments, then the LSD test was performed. The results showed that rhodamine B was significantly increased the time of estrous cycle (P<0.05).
Keywords: Rhodamin B, estrous cycle, mice (Mus musculus L.)